Impact of institutional educational program on compliance of implementation of surviving sepsis campaign guidelines, total ICU and hospital mortality - Agrawal, Kapil H.; Ausim, Syed M.; Awode, Rhishikesh M.; Katiyar, Sarika R. (International Journal of Research in Medical Sciences, 2017)
Background: To determine whether educational program based on the surviving sepsis campaign (SSC) guidelines affects the compliance of implementation of SSC guidelines, total ICU and hospital mortality. Methods: A prospective observational study conducted in adult patients with severe sepsis or septic shock admitted to 11 bedded adult medical and surgical ICU of Bhopal Memorial Hospital and Research Centre, Bhopal, Madhya Pradesh, India. In pre-education period all patients in ICU were daily screened according to severe sepsis screening tool and followed up daily during their entire period of ICU stay. Outcome measures were compliance of implementation of SSC guidelines, total ICU and hospital mortality noted. Education program of resident doctors of the ICU, emergency department, medical and surgical units was carried out. Post-education period data noted similar to the pre-education period. Comparative statistics applied by using Chi-square test and paired Student t-test. Results: Compliance to all resuscitative measures in SSC guideline both 3 hour and 6 hour bundles significantly improved after education program (P-value 0.014). In pre-education period 33.3% patients were treated with complete implementation of SSC Guidelines Bundles compared to 63.6% in post-education period. Total ICU mortality and hospital mortality did not change significantly after education program during study period. Total ICU mortality during pre-education period was 29.52% as compared to 25.45% in post-education period (P-value 0.44) while total hospital mortality in pre-education period was 5.18% as compared to 5.62% in post-education period (P-value 0.07). Conclusions: The Institutional educational program has significant impact on increasing compliance to both 3 hour and 6 hour bundles in SSC guideline but failed to show any significant impact on decreasing overall total ICU and hospital mortality.